Analyzing Tourism Behaviours and Tourism Autonomy in the Global Market: Cases of Nepal’s Pashupatinath Temple and Korean DMZ - Thapa, Abhijeet (Nepalese Culture, 2021)
Tourist guides and travel agents in Nepal had been selling Hindu funeral rite as tourism package to the tourists in the Pashupatinath premises until the Covid pandemic hit the global market paralyzing tourism to a woeful state. However, soon after the dangers are curbed this will continue on a surging pace hopefully. Non- Hindus do not get to enter the temple but westerners and tourists throng here to see the extraordinary funeral rite which surely can be put as popular product that has outgrown its small-dome in this World heritage site. Unlike the ritual niche package of the Nepalese, in another part of the world, South Koreans have been selling "border-sights" in a strip of land between North Korea and South Korea. The notorious infiltration tunnels there in are so said to have been clandestinely built by North Korea to sneak its army into Seoul and capture South Korea by surprise which were found out after the secret was spilled by a North Korean involved in the project. Until now, 4 such tunnels have been found but it is believed that there are numerous. As of now, there are no clear clarifications and political confessions from North Korea about these. This paper unfurls through writer’s own experiences in different roles (as a tourist guide and as a tourist) at these two entirely different sites to dig upon how tourism products are sold, consumed and popularized in the tourism sectors. The findings also reveal how states as hosts have begun inducing captivating packages in unusual destinations that turn tourists into consumers. But there are unanswered question of ethics and tourism strategies.